Relationship between Ankyloglossia and Breastfeeding: A Bibliometric Review - Daniela Novaes Soares; Fernanda Barja-Fidalgo; Tatiana Kelly da Silva Fidalgo (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess global trends in the publication of studies investigating the association between ankyloglossia and breastfeeding. Material and Methods: An electronic search was performed in the Scopus database without restrictions. Observational studies and clinical trials were included. Bibliometric indices such as publication year, authors, co-authors, journals, field of knowledge, countries, and the most cited keywords were analyzed using the VOSviewer program. Results: The search retrieved 350 studies, and 68 were selected. The first article was published in 2000 in the United States. The United States presented the highest number of publications (n=21), followed by Brazil (n=9) and the United Kingdom (n=9). An increase in publications on this theme was observed in 2013; 2021 was the year with the highest number of publications (n=14). The most common word was "frenulum". The authors with the highest number of publications were Botze and Dollbert from Israel (n=3), Ghaheri, and Mace from the United States (n=3). Among the journals, "Breastfeeding Medicine" presented the highest number of publications (n=7), followed by the "International Journal of Pediatric Otorhinolaryngology" (n=6), "CODAS" (n=5), "Journal of Human Lactation" (n=4) and "Pediatrics" (n=3); the latter published the top-cited studies, with 412 citations. Conclusion: There has been an increase in recent articles evaluating the correlation between ankyloglossia and breastfeeding, indicating the growing interest of researchers in this field.